Decreased ventricular systolic function in chemotherapy-naive patients with acute myeloid leukemia: a three-dimensional speckle-tracking echocardiography study - Zhang, Yichan; Tan, Yuting; Liu, Tianshu; Fu, Yanan; Lin, Yixia; Shi, Jiawei; Zhang, Yanting; Deng, Wenhui; He, Shukun; Yang, Yali; Lv, Qing; Zhang, Li; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The relationship between acute myeloid leukemia (AML) or acute lymphoblastic leukemia (ALL) and cardiac function is not well established. This study aimed to evaluate whether AML patients exist early myocardial damages prior to chemotherapy and to investigate its association with cardiovascular biomarkers. Methods: Conventional echocardiography and three-dimensional speckle-tracking strain analysis were performed prospectively in 72 acute leukemia (AL) patients before any chemotherapy therapy (of whom 44 were AML patients, 28 ALL patients). The results were compared with those from 58 control group matched for age and gender. Results: There were no significant differences in conventional biventricular systolic function parameters between AL patients and controls. The left ventricular global longitudinal strain (LVGLS) and right ventricular free wall longitudinal strain (RVFWLS) were significantly lower in AL patients (-23.0 ± 1.4% vs -24.1 ± 1.3% and -27.9 ± 7.1% vs -33.0 ± 4.6%, respectively, P < 0.001 for all). Compared with ALL patients, AML patients had lower LVGLS and RVFWLS (-22.7 ± 1.3% vs -23.5 ± 1.6% and -26.2 ± 7.6% vs -30.4 ± 5.5%, respectively, P < 0.05 for all). LVGLS was lower in ALL patients compared with controls (-23.5 ± 1.6% vs -24.7 ± 1.4%, P < 0.05), however, there was no difference in right ventricular systolic function parameters between the two groups. LVGLS in AL patients was independently correlated with left ventricular ejection fraction (LVEF) and the absolute number of circulating lymphocytes. Conclusions: Our findings suggest that baseline myocardial systolic function is lower in AL patients than controls. AML patients had lower baseline LVGLS and RVFWLS than controls and ALL patients. The decreased LVGLS is correlated with LVEF and the absolute number of circulating lymphocytes.